Iodide ions enhancing sulfamerazine degradation by horseradish peroxidase/H2O2: Degradation products, degradation mechanism and toxicity assessment. (20th February 2022) - Wang, Jiali; Shu, Zhao; Chen, Zhennan; Su, Jixin; Liu, Chunguang
Abstract: Biocatalytic treatment using horseradish peroxidase (HRP) is a sustainable technology to remove antibiotics from wastewater. In order to improve removal efficiency, a HRP/H2 O2 /I − system has been developed for sulfadiazine (SMR) degradation. The addition of 1.5 mM iodide ion (I − ) significantly increases the degradation efficiency of SMR from 16.06% to 90.91% by HRP/H2 O2, following pseudo-first-order kinetics (r 2  = 0.975). Analysis of SMR degradation products by high resolution Q-TOF mass spectrometry shows that SMR degradation mainly involves in iodine substitution, oxidation and polymerization. Iodo-sulfadiazine, as the main intermediates, is gradually degraded overtime. The main mechanism of iodide ion promoting SMR degradation is closely related to the existing forms of iodine. Under the action of HRP/H2 O2, iodide ions are converted into iodine and hypoiodic ions, which are easier to react with SMR by substitution. Molecular simulation shows that iodo-sulfadiazine is easier to bind HRP than SMR due to its stronger binding energy, thus enhancing SMR degradation. The toxicity of degradation products to Bacillus subtilis (model bacteria widely existing in the environment) is as follows: final degradation products < intermediate degradation products < SMR. This study can provide technical support for developing a feasible and sustainable sulfanilamide-containing wastewater treatment solution, and provide reference for the fate and risk assessment of sulfonamide antibiotics in the environment. Graphical abstract: Image 1 Highlights: I − markedly enhances SMR degradation by HRP/H2 O2 depending on I − concentration. Some SMR are first formed into I-substituted products and then are degraded rapidly. The antibacterial effect of the degradation products and the iodate is weakened.